EFFECT OF ACID CONCENTRATION ON CHARACTERS OF SILICA GEL SYNTHESIZED FROM SODIUM SILICATE - Nuryono Nuryono; Narsito Narsito (Universitas Gadjah Mada, 2005)
In this research, synthesis and characterization of silica gel from sodium silicate through sol-gel process using H2SO4, HCl, and citric acid have been investigated. Synthesis was carried out by mixing and stirring 20 mL of H2SO4, HCl or citric acid at certain concentration with 50 mL of sodium silicate solution (Na2O 0.17 M and SiO2 0.61 M) for one hour and let to form gel. The gel was washed with distillated water, and dried in an oven at 100 oC. Characterization of silica gel was carried out by determination of acidity, water adsorption capacity, and water content. Identification of functional group and structure were identified using x-ray diffractometer (XRD) and infrared (IR) spectrophotometer, respectively. Results showed that at a range of investigated concentration (0.6 - 3.0 M) the increase of concentration, formation of gel with H2SO4 tended to be faster, but with HCl and citric acid to be slower. The increase of acid concentration caused water content, water adsorption capacity, and acidity of the silica gel resulted with HCl and citric acid tended to be increased, increased, and increased, but with H2SO4 to be decreased, increased, and decreased, respectively. Based on the IR spectra and XRD data, it could concluded that the synthetic silica gels contained silanol (Si-OH) and siloxane (Si-O-Si) and were amorphous, showing similar pattern to kieselgel G 60 produced by Merck.